ASSESSMENT OF THE ECOLOGICAL SUSTAINABILITY OF AGRICULTURAL LAND USE IN THE TERRITORIAL STRUCTURE OF REGION - Halyna DUDYCH; Lesia DUDYCH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article is devoted improves method of the assessment of the ecological sustainability of agricultural land use in the territorial structure of region. Approbation of this method was carried out on the example of the districts of the Lviv region, located in the western part of Ukraine. The analysis of ecological parameters and modern structure of lands of the territory of Lviv region is presented. Based on the analysis of the coefficients of ecological sustainability of agricultural land use, three groups of districts have been identified, depending on the level of this indicator: stable, average sustainability, low sustainability. Using correlation-regression analysis, we established the relationship between ecological parameters of the organization of the territory and humus content, as well as the normative-monetary valuation of land, using the example of Lviv region districts. The proposed method for assessing the ecological sustainability use can be an integral part of the ecological passport of the territory, which makes it possible to consider the environmental factors that have resulted in the result of the assessment in combination and interdependence. The application of the proposed methodology makes it possible to choose the best variant of the organization of land use in agrosphere, which will increase the efficiency of production, as well as optimization of natural ecosystems.